Dänischwerden und Dänischsein im Landesteil Schleswig - Zugehörigkeiten und Verortungsprozesse - Bittlinger, Levke (Universitätsverlag Göttingen, 2020)
Pointing at ambivalences and inconsistencies, contradictory expectations, nationalistic and pragmatic points of view, this study shows parts of the becoming, being and remaining (or not) Danish in Germany. Using qualitative methods and a constructivist approach, Levke Bittlinger examines questions of minority- and nationhood with regard to actors and the main institutions within the Danish minority in the Southern Schleswig region. The research ranges from the backgrounds of people becoming Danish in the postwar time to today's parents sending their children to Danish institutions for social and material matters. The study reaches from the analysis of the role of the Danish school system, the cultural association including their expectations on new Danish people concerning their integration into the minority to the importance of symbols, practices and historical myths for constructing a minority belonging.